2010
DOI: 10.2319/081009-454.1
|View full text |Cite
|
Sign up to set email alerts
|

Self-Ligating Brackets in Orthodontics

Abstract: Objective: To evaluate the clinical differences in relation to the use of self-ligating brackets in orthodontics. Materials and Methods: Electronic databases were searched; no restrictions relating to publication status or language of publication were applied. Randomized controlled trials (RCTs) and controlled clinical trials (CCTs) investigating the influence of bracket type on alignment efficiency, subjective pain experience, bond failure rate, arch dimensional changes, rate of orthodontic space closure, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
21

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 26 publications
4
98
0
21
Order By: Relevance
“…On the other hand, more recent studies by Miles [9] and Fleming et al [10] found no improvement in the efficiency of the treatment, although Pandis et al [11] verified that slight crowding was eliminated more rapidly with a Damon2 system than with conventional brackets in the hands of one same operator [11]. In two recent studies, Chen et al [12] and Fleming PS and Johal A [13] carried out a systematic review aiming at verifying clinical evidence on the impact of self-ligating systems in orthodontic treatments. In the first study [11], the authors concluded that, despite the claims as to the clinical superiority of self-ligating brackets, and the fact that they seem to have significant advantages regarding chair time and incisor proclination (less than 1.5 degrees), no significant differences were found in the time of treatment and in occlusal characteristics between the two kinds of brackets.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, more recent studies by Miles [9] and Fleming et al [10] found no improvement in the efficiency of the treatment, although Pandis et al [11] verified that slight crowding was eliminated more rapidly with a Damon2 system than with conventional brackets in the hands of one same operator [11]. In two recent studies, Chen et al [12] and Fleming PS and Johal A [13] carried out a systematic review aiming at verifying clinical evidence on the impact of self-ligating systems in orthodontic treatments. In the first study [11], the authors concluded that, despite the claims as to the clinical superiority of self-ligating brackets, and the fact that they seem to have significant advantages regarding chair time and incisor proclination (less than 1.5 degrees), no significant differences were found in the time of treatment and in occlusal characteristics between the two kinds of brackets.…”
Section: Introductionmentioning
confidence: 96%
“…2 When compared with conventional brackets, several advantages of self-ligating brackets have been claimed, including faster ligation, reduced friction, and faster treatment time with reduced number of visits and less pain. [3][4][5][6] In laboratory setups, self-ligating brackets have demonstrated reduced friction compared with conventional brackets tied with modules. 7,8 In other studies, however, reduced frictional resistance with self-ligating brackets compared with conventional brackets was found only in combination with certain wires.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 There is still controversy and limited knowledge regarding the evidence for reduced overall treatment time with self-ligating brackets, and the need for prospective randomized studies is obvious. [3][4][5] Recent prospective randomized studies have shown that selfligating brackets do not reduce overall treatment time, neither in terms of number of visits nor treatment outcome. 19,20 The need for further evaluation of the overall efficiency of self-ligating brackets in daily orthodontic clinical work is thus important.…”
Section: Introductionmentioning
confidence: 99%
“…: La photobiomodulation laser semble pouvoir atténuer la douleur initiale à court terme [15,27] [9,10,26] ont montré qu'il n'existe pas de données publiées probantes permettant d'affirmer que l'emploi des brackets autoligaturants réduit la douleur du patient, raccourcit la durée totale du traitement, procure un résultat plus stable ou meilleur sur les plans esthétique ou occlusal, ou diminue le recours aux avulsions dentaires. Quelle est votre opinion et quelles sont les conclusions de vos récentes études [13,59], consacrées à la comparaison entre brackets autoligaturants et brackets conventionnels ?…”
Section: Thérapie Laser De Faible Intensitéunclassified